Enhancing Climate Resilience and Productivity in Cambodia Mekong Deltas - Sean, Vichet (WorldFish, 2024)
On November 26, 2024, key findings from research in the National Dialogue on Integrated Decentralized Food System Governance were presented. Key stakeholders were brought together at the Council of Ministers in Phnom Penh. This event aimed to develop innovative strategies to improve food security, nutrition, and agricultural resilience in the Mekong Delta, Cambodia.